1995
DOI: 10.1016/0014-5793(95)01356-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of bacteriorhodopsin in oocytes allows direct measurement of voltage dependence of light induced H+ pumping

Abstract: We report on the first successful expression of the light driven H ÷ pump, bacteriorhodopsin, into the plasma membrane of oocytes from Xenopus laevis. The light induced photocurrents which reflect the pumping of H ÷ by BR were analysed under voltage clamp conditions. At least 100 active BR molecules per/~m 2 were expressed in the plasma membrane so that both the voltage clamp and giant patch clump method could be applied. We show that H + pumping by BR is modulated by the membrane potential, i.e. the pump curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 23 publications
5
62
1
1
Order By: Relevance
“…Similarly, 0.1-to 0.3-unit ⌬pH changes can result in a similar accumulation ratio. Such modest changes in the membrane potential or ⌬pH are consistent with the proton-pumping capacity of PR (27,29), suggesting that illumination leads to increased lactate uptake, increased reduction of electron carriers such as NAD ϩ /NADH and menaquinone/menaquinol, and a need for faster regeneration of oxidized electron carriers (Fig. 7).…”
Section: ϫ2supporting
confidence: 58%
“…Similarly, 0.1-to 0.3-unit ⌬pH changes can result in a similar accumulation ratio. Such modest changes in the membrane potential or ⌬pH are consistent with the proton-pumping capacity of PR (27,29), suggesting that illumination leads to increased lactate uptake, increased reduction of electron carriers such as NAD ϩ /NADH and menaquinone/menaquinol, and a need for faster regeneration of oxidized electron carriers (Fig. 7).…”
Section: ϫ2supporting
confidence: 58%
“…10A. Nonetheless, we elected to present the majority of our results using the only available quantitative measurement of photosensitive channel density (Nagel et al 1995), albeit from bacteriorhodopsin in Xenopus oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The ChR2 model was typically inserted in all compartments of the neuron model, with a uniform ChR2 channel density of 130 m Ϫ2 (Nagel et al 1995). To simulate the effect of nonuniform distributions, ChR2 was distributed either in specific compartments (Table 2), or by distributing its density based on distance from the soma (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The voltage-clamp setup was essentially that of Nagel et al (1,2). If not mentioned otherwise, the membrane potential was clamped at Ϫ40 mV (50 Hz signal filtering) in the case of pSRII, pSRII-F86D, and pSRII(F86D)͞pHtrII and at Ϫ20 mV (20 Hz signal filtering) for SRI and SRI͞HtrI.…”
Section: Methodsmentioning
confidence: 99%
“…In previous work, it has been demonstrated that bacteriorhodopsin (BR) from Halobacterium salinarum could also be functionally expressed into the plasma membrane of oocytes, which allowed the elucidation of the electrogenic characteristics of this proton pump under well-defined voltageclamp conditions (1,2). This work indicated that the other members of the bacterial rhodopsin family, the chloride pump halorhodopsin, and the sensory rhodopsins can also be analyzed by this approach.…”
mentioning
confidence: 97%